Narrativas infantis: o que nos contam as crianças de suas experiências no hospital e na classe hospitalar - Rocha, Simone Maria da (2012)
This dissertation focuses on the narratives of children hospitalized with chronic diseases. The overall goal is to deduce, from the look of the child health care, hospital class contributions to the process of school inclusion. The research is part of the qualitative ethnographical approach and is based on the principles and research methods (auto)biographical in education and schooling in hospital. Participated in the investigation 05(five) children, aged between 06 (six) and 12 (twelve) years of age, treated at the Center for Children s Onco-Hematology, Varela Santiago Children s Hospital in Natal-RN. The corpus used for the analysis comprises five (05) narrative interviews, 03 (three) drawings made by children as well as records in the researcher s field diary. The sources were collected during the months of August 2010 to February 2011. The analysis revealed that the inclusion of the hospital class, and ensure the right to education, contributes to the construction of strategies for coping with illness and hospitalization, as it promotes autonomy, comfort, playfulness and self-knowledge, the rand the world, easing the stress of hospitalization. The figure of the teacher took the class hospital in the voices of children, a reliever and minimizing the role of double exclusion that cause illness and hospitalization, showing the contributions to (re) construction of identity and subjectivity constitution strengthened. The children interviewed said that the hospital class leave the hospital more cheerful. The playfulness and learning experiences in the hospital are seen by children as actions that go beyond the physical treatment of the disease, since it provides them with acceptance and understanding of hospitalization and illness, to give them affective security and emotional. In conclusion, the narratives of children confirm that the service class hospital ensures continuity of schooling, but they reveal, namely, that this service provides them socialization among peers and with adults, strengthening the emotional, social and cognitive biopsychosocial perspective of attention